The Impact of Regulatory Framework on Risk Management in China’s Securities Market: A Case Study of Investment Funds - Hu, Ying (Journal of Ecohumanism, 2024)
This study focuses on the impact of the regulatory framework on the risk management practices of investment funds in China. By analysing key regulatory policy changes between 2018 and 2023, we explore how these changes have shaped the risk management strategies and performance of investment funds. The study adopts a mixed-method approach, combining policy text analysis and empirical studies of fund performance, to assess the regulatory effects and make policy recommendations. The study finds that changes in the regulatory framework have significantly affected the risk management practices of investment funds. Specifically, 1) enhanced liquidity risk management requirements have prompted funds to adopt more advanced risk assessment models; 2) regulations on the use of derivatives have led to the development of more complex hedging strategies; and 3) improvements in the information disclosure system have increased the transparency of fund risks, but also increased compliance costs. The main contributions of this study include: 1) proposing an analytical framework for assessing the impact of regulatory policies on fund risk management; 2) quantifying the impact of regulatory changes on fund risk-adjusted returns; and 3) providing an in-depth analysis of how fund managers have adapted to the new regulatory environment. These findings not only have important implications for the regulation of China’s securities market, but also provide practical guidance for investors and fund managers.